The Influence of a Lattice-Like Pattern of Inclusions on the Attenuation Properties of Metaconcrete - Briccola, Deborah; Tomasin, Marianna; Netti, Teresa; Pandolfi, Anna (Frontiers in Materials, 2019)
The attenuation performance of metaconcrete specimens characterized by a lattice-like pattern of bi-material resonant inclusions was verified through nondestructive transmission tests spanning the sonic range of frequencies. Seven cubic specimens of metaconcrete with regularly disposed resonant inclusions have been cast from a standard concrete matrix. Inclusions were regularly spaced and symmetrically disposed in a three-dimensional setting. Specimens differ in terms of inclusion spacing, controlled by varying the number of inclusions (0, 8, 27, and 64) and the cement cover. Three-month cured specimens have been tested along the three symmetry axes, under a sinusoidal excitation with four linearly variable frequency sweeping ranges centered at the eigenfrequencies of the inclusions, to assess the relevance of inclusion packing and arrangement on the dynamic behavior of metaconcrete. With respect to the plain concrete specimen, all engineered specimens showed a marked attenuation of the transmitted signal at a frequency close or very close to the theoretical eigenfrequency of the resonant inclusion. The attenuation was weakly dependent on the density of the inclusions and apparently not affected by interspacing, cement cover, and direction of the excitation along the axes of the specimen. Experimental results confirmed the behavior of metaconcrete as predicted by theoretical investigations, and further proved that the attenuation properties of metaconcrete are due to the resonant behavior of the inclusions.